2016
DOI: 10.15171/jlms.2016.40
|View full text |Cite
|
Sign up to set email alerts
|

A Split Mouth Randomized Clinical Comparative Study to Evaluate the Efficacy of Gingival Depigmentation Procedure Using Conventional Scalpel Technique or Diode Laser

Abstract: Please cite this article as follows: Suragimath G, Lohana MH, Varma S. A split mouth randomized clinical comparative study to evaluate the efficacy of gingival depigmentation procedure using conventional scalpel technique or diode laser. J Lasers Med Sci. 2016;7(4):227-232. doi:10.15171/jlms.2016.40. IntroductionA smile is an expression denoting pleasure, sociability, happiness or amusement and can reflect self-confidence of an individual. A smile seems to have a favorable influence upon others and makes one l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
35
0
10

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(48 citation statements)
references
References 16 publications
3
35
0
10
Order By: Relevance
“…Application of the laser in pulsed mode prevents overheating of surrounding tissues that may cause necrosis and jeopardize healing. Taking into consideration the previously published studies,[ 3 4 14 15 ] diode laser was used in continuous mode in this study knowing the fact that it may penetrate deeper and affect connective tissue as well. That's why, the evaluations were also made at weeks 4 and 12.…”
Section: Discussionmentioning
confidence: 99%
“…Application of the laser in pulsed mode prevents overheating of surrounding tissues that may cause necrosis and jeopardize healing. Taking into consideration the previously published studies,[ 3 4 14 15 ] diode laser was used in continuous mode in this study knowing the fact that it may penetrate deeper and affect connective tissue as well. That's why, the evaluations were also made at weeks 4 and 12.…”
Section: Discussionmentioning
confidence: 99%
“…The smile is a manifestation of self-confidence that involves aesthetic and psychological factors, and it includes teeth, lips, and gingival tissue. The color of the gingival tissue is usually pink, but it may be darker in some cases, also known as gingival hyperpigmentation (Suragimath et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Gingival hyperpigmentation causes aesthetic complaints, especially from patients with a gummy smile or excessive gingival exposure when smiling. The depigmentation treatment aims to remove melanin, and the techniques proposed include the scalpel technique (gold standard), gingivectomy, grafting, electrosurgery, cryosurgery, and laser (Suragimath et al;Bakutra et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Suragimath G et al conducted a randomized clinical comparative study to assess the effectiveness of the procedure for depigmentation of the gums by using the conventional scalpel and diode laser (980 nm) and showed that depigmentation of the gums was equally effective in both the scalpel and laser methods. However, the areas treated with a laser caused less pain in patients [10]. Alhabashneh R. et al conducted a 6-month trial and showed equal efficacy in the treatment of hyperpigmentation of the gums with a laser and a scalpel, postoperative pain perception and the time required for treatment were also the same, with laser therapy requiring more advanced technology and higher financial costs [11].…”
Section: Resultsmentioning
confidence: 99%